Unemployment as a Social Norm: Psychological Evidence from Panel Data - Clark, Andrew E. (Journal of Labor Economics, 2003)
This article proposes a formal model of migration in which workers are heterogeneous and markets are stochastically correlated. We derive and characterize the optimal migration pattern of a family. We show that migration can take place even when migrants earn less abroad and, surprisingly, when earnings in the foreign country are riskier for every member of the family. Moreover, it may well be an optimal arrangement to have only dependents migrate, thus rationalizing the recent dependent-oriented migration flows from places like Hong Kong and Taiwan. We provide some evidence in support of our theory.